Flawed perfection : what it means to be human & why it matters for culture, politics, and law - Brauch, Jeffrey A. (Lexham Press, 2017)
In order to understand the problems that face the world, you have to understand human nature...It is only by understanding our nature correctly that we can recognize our profound value as God's good creation despite our fallen condition, and uphold our equal human rights regardless of our differences. --Publisher